Case Identification and Risk Factors of Enterobius Vermicularis Infection in Children at the Coastal Area - Aldiana Astuti; Novian Agni Yudhaswara; Cezia Bernitha Ambesa; Michaael B Bia; Meliance Bria (Poltekkes Kemenkes Kupang, 2026)
Enterobiasis is an infectious disease caused by Oxyuris vermicularis (Enterobius vermicularis) or pinworms and is a non-STH (non-Soil Transmitted Helminth) intestinal worm that can move from one individual to another without the need for transmission through the soil and is widespread in children and toddlers. In Indonesia, the prevalence of Enterobiasis is quite high, this is because Indonesia is a country with a tropical climate, high temperature, humidity, social economic factors and poor sanitation, making it suitable for the development of pinworms. Children with poor hygiene behavior (PHBS), such as rarely changing underwear, and not washing hands after the toilet are at risk of contracting pinworms. Children who live around the coast still have a lack of knowledge of the importance of maintaining personal hygiene and also a lack of knowledge about the dangers of helminthiasis and the examination and treatment of helminthiasis. The method used in this study is descriptive. Respondents in this study included 24 people with the number of female respondents at 54% and men at 46%. The results of Enterobius vermicularis examination in children aged 3-9 years living in the coastal area of Lasiana beach obtained 21% of children positive for enterobiasis and 79% of children negative for Enterobiasis. The level of parental knowledge, environmental sanitation conditions, and children's personal hygiene is pretty good